2009
DOI: 10.5414/cpp47071
|View full text |Cite
|
Sign up to set email alerts
|

A combination of cetirizine and pseudoephedrine has therapeutic benefits when compared to single drug treatment in allergic rhinitis

Abstract: Antihistamines and nasal decongestants are well-established therapeutics in allergic rhinitis. However, no data are available which directly compare the effect size of the single substances with their combination in a single study including placebo (PLA) treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The chosen pollen concentration mimics the natural condition because pollen counts of several thousands per cubic metre have been reported when measurements are performed over a meadow [19] (and own unpublished data). It is important to note that the study population was not pre‐selected according to their symptom scores during a screening exposure visit, which explains why the average TNSS is lower compared with other ECC studies where pre‐selection of responders is part of the screening procedure in order to reduce the variability of the outcome measure [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…The chosen pollen concentration mimics the natural condition because pollen counts of several thousands per cubic metre have been reported when measurements are performed over a meadow [19] (and own unpublished data). It is important to note that the study population was not pre‐selected according to their symptom scores during a screening exposure visit, which explains why the average TNSS is lower compared with other ECC studies where pre‐selection of responders is part of the screening procedure in order to reduce the variability of the outcome measure [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the severity of disease, the mainstay treatments for AR are oral or topical H1-antihistamines and intranasal corticosteroids (INS), with INS reported to be the most efficacious currently available treatment [7,8]. Despite treatment, many patients may still suffer some residual symptoms [9,10], and it has been reported that up to 1 in 5 patients with AR remain symptomatic when treated with the best available pharmacotherapy [11].…”
Section: Introductionmentioning
confidence: 99%
“…An example of a typical study design for evaluating an acute treatment effect is a double‐blind, placebo‐controlled, four‐way crossover study, in which placebo, an antihistamine, a decongestant or a combination of both was given 2 hours after starting the allergen challenge in the ACC . Within the first hour following the treatment, a clear separation of the TNSS was seen in the different treatment arms (Fig.…”
Section: Experience With the Fraunhofer Challenge Chambermentioning
confidence: 99%